High prevalence of colistin heteroresistance in specific species and lineages of Enterobacter cloacae complex derived from human clinical specimens - Shota Fukuzawa; Toyotaka Sato; Kotaro Aoki; Soh Yamamoto; Noriko Ogasawara; Chie Nakajima; Yasuhiko Suzuki; Motohiro Horiuchi; Satoshi Takahashi; Shin-ichi Yokota (BMC, 2023)
Abstract Background Colistin (CST) is a last-line drug for multidrug-resistant Gram-negative bacterial infections. CST-heteroresistant Enterobacter cloacae complex (ECC) has been isolated. However, integrated analysis of epidemiology and resistance mechanisms based on the complete ECC species identification has not been performed. Methods Clinical isolates identified as "E. cloacae complex" by MALDI-TOF MS Biotyper Compass in a university hospital in Japan were analyzed. Minimum inhibitory concentrations of CST were determined by the broth microdilution method. The population analysis profiling (PAP) was performed for detecting the heteroresistant phenotype. The heat shock protein 60 (hsp60) cluster was determined from its partial nucleotide sequence. From the data of whole-genome sequencing, average nucleotide identity (ANI) for determining ECC species, multilocus sequence type, core genome single-nucleotide-polymorphism-based phylogenetic analysis were performed. phoPQ-, eptA-, and arnT-deleted mutants were established to evaluate the mechanism underlying colistin heteroresistance. The arnT mRNA expression levels were determined by reverse transcription quantitative PCR. Results Thirty-eight CST-resistant isolates, all of which exhibited the heteroresistant phenotype by PAP, were found from 138 ECC clinical isolates (27.5%). The prevalence of CST-resistant isolates did not significantly differ among the origin of specimens (29.0%, 27.8%, and 20.2% for respiratory, urine, and blood specimens, respectively). hsp60 clusters, core genome phylogeny, and ANI revealed that the CST-heteroresistant isolates were found in all or most of Enterobacter roggenkampii (hsp60 cluster IV), Enterobacter kobei (cluster II), Enterobacter chuandaensis (clusters III and IX), and Enterobacter cloacae subspecies (clusters XI and XII). No heteroresistant isolates were found in Enterobacter hormaechei subspecies (clusters VIII, VI, and III) and Enterobacter ludwigii (cluster V). CST-induced mRNA upregulation of arnT, which encodes 4-amino-4-deoxy-l-arabinose transferase, was observed in the CST-heteroresistant isolates, and it is mediated by phoPQ pathway. Isolates possessing mcr-9 and mcr-10 (3.6% and 5.6% of total ECC isolates, respectively) exhibited similar CST susceptibility and PAP compared with mcr-negative isolates. Conclusions Significant prevalence (approximately 28%) of CST heteroresistance is observed in ECC clinical isolates, and they are accumulated in specific species and lineages. Heteroresistance is occurred by upregulation of arnT mRNA induced by CST. Acquisition of mcr genes contributes less to CST resistance in ECC.